Phenotypic, Technological, Safety, and Genomic Profiles of Gamma-Aminobutyric Acid-Producing Lactococcus lactis and Streptococcus thermophilus Strains Isolated from Cow’s Milk - Valenzuela López, José Alejandro (2024)
Gamma-aminobutyric acid (GABA)-producing lactic acid bacteria (LAB) can be used as starters in the development of GABA-enriched functional fermented foods. In this work, four GABA-producing strains each of Lactococcus lactis and Streptococcus thermophilus species were isolated from cow’s milk, and their phenotypic, technological, and safety profiles determined. Genome analysis provided genetic support for the majority of the analyzed traits, namely, GABA production, growth in milk, and the absence of genes of concern. The operon harboring the glutamate decarboxylase gene (gadB) was chromosomally encoded in all strains and showed the same gene content and gene order as those reported, respectively, for L. lactis and S. thermophilus. In the latter species, the operon was flanked (as in most strains of this species) by complete or truncated copies of insertion sequences (IS), suggesting recent acquisition through horizontal gene transfer. The genomes of three L. lactis and two S. thermophilus strains showed a gene encoding a caseinolytic proteinase (PrtP in L. lactis and PrtS in S. thermophilus). Of these, all but one grew in milk, forming a coagulum of good appearance and an appealing acidic flavor and taste. They also produced GABA in milk supplemented with monosodium glutamate. Two L. lactis strains were identified as belonging to the biovar. diacetylactis, utilized citrate from milk, and produced significant amounts of acetoin. None of the strains showed any noticeable antibiotic resistance, nor did their genomes harbor transferable antibiotic resistance genes or genes involved in toxicity, virulence, or pathogenicity. Altogether these results suggest that all eight strains may be considered candidates for use as starters or components of mixed LAB cultures for the manufacture of GABA-enriched fermented dairy products.